Synthesis, characterization and electrochemistry of novel differently octasubstituted phthalocyanines - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
We describe the complete synthesis of differently substituted multifunctional metallo phthalocyanines (MPcs) (M = Ni, Zn, Cc) bearing four 2'-aminophenylsulfanyl or 2-aminophenoxy moieties and four chloro atoms on peripheral positions. The synthesis started from the corresponding anhydrous metal salts and differently substituted [4-(2'-aminophenylsulfanyl)-5-chlorobenzene-1,2dicarbonitrile] (2a) and [4-(2-aminophenoxy)-5-chlorobenzene-1,2-di-carbo nitrile] (2b), and the products were separated by HPLC. These multifunctional amino substituents serve as strong binding sites for further reactions after phthalocyanine formation, such as Schiff-bases, and provide solubility of the phthalocyanines in organic solvents (THF, CHCl3 and CH2Cl2). The newly synthesized compounds have been characterized by elemental analysis, FTIR, H-1 NMR, MS (EI and FAB), UV-Vis and atomic absorption spectroscopy. Electrochemical studies reveal that CoPc (6a) has two metal and four ligand-based redox processes while NiPc (4a) and ZnPc (5b) show three ligand-based reduction processes. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: phthalocyanines; phthalonitrile derivatives; electrochemistry; nickel; zinc; cobalt; 16-MEMBERED DIAZADITHIA MACROCYCLES; METALLOPHTHALOCYANINES; SUBSTITUENTS